Magnetic hybrid materials interact with biological matrices - Gräfe, Christine; Müller, Elena K.; Gresing, Lennart; Weidner, Andreas; Radon, Patricia; Friedrich, Ralf P.; Alexiou, Christoph; Wiekhorst, Frank; Dutz, Silvio; Clement, Joachim H. (Magnetic Hybrid-Materials: Multi-scale Modelling, Synthesis, and Applications, 2021)
Magnetic hybrid materials are a promising group of substances. Their interaction with matrices is challenging with regard to the underlying physical and chemical mechanisms. But thinking matrices as biological membranes or even structured cell layers they become interesting with regard to potential biomedical applications. Therefore, we established in vitro blood-organ barrier models to study the interaction and processing of superparamagnetic iron oxide nanoparticles (SPIONs) with these cellular structures in the presence of a magnetic field gradient. A one-cell-type-based blood-brain barrier model was used to investigate the attachment and uptake mechanisms of differentially charged magnetic hybrid materials. Inhibition of clathrin-dependent endocytosis and F-actin depolymerization led to a dramatic reduction of cellular uptake. Furthermore, the subsequent transportation of SPIONs through the barrier and the ability to detect these particles was of interest. Negatively charged SPIONs could be detected behind the barrier as well as in a reporter cell line. These observations could be confirmed with a two-cell-type-based blood-placenta barrier model. While positively charged SPIONs heavily interact with the apical cell layer, neutrally charged SPIONs showed a retarded interaction behavior. Behind the detected. Finally, the transfer of the in vitro blood-placenta model in a microfluidic biochip allows the integration of shear stress into the system. Even without particle accumulation in a magnetic field gradient, the negatively charged SPIONs were detectable behind the barrier. In conclusion, in vitro blood-organ barrier models allow the broad investigation of magnetic hybrid materials with regard to biocompatibility, cell interaction, and transfer through cell layers on their way to biomedical application.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biocompatibility; Magnetic nanoparticles; Particle-cell interaction